2016
DOI: 10.1080/23273798.2016.1175649
|View full text |Cite
|
Sign up to set email alerts
|

How children and adults encode causative events cross-linguistically: implications for language production and attention

Abstract: This study investigates the implications of language-specific constraints on linguistic event encoding for the description and on-line inspection of causative events. English-speaking and Greek-speaking adults, 3-year-olds, and 4-year-olds viewed and described causative events, which are composed of Means and Result subevents, in an eyetracking study. The results demonstrate cross-linguistic differences in the informational content of causative event descriptions: Greek speakers across age groups were more lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 73 publications
(156 reference statements)
2
23
0
Order By: Relevance
“…Similarly, their event memory was boosted after verbalization of the scenes, independent of the specific forms uttered. This is a novel finding in the “thinking for speaking” literature: Whereas there is ample evidence for online attention biases induced by selection and retrieval of specific linguistic forms and structures (e.g., Bunger et al., ; Flecken, Carroll, Weimar, & van Stutterheim, ; Hendriks, Hickmann, & Demagny, ; Papafragou & Selimis, ; Papafragou et al., ; Slobin, ; Soroli & Hickmann, ), the present data suggest that these effects are not limited to such contexts. Here, a language‐specific effect surfaces regardless of the specific form in the linguistic output; it is driven by general requirements of Estonian grammar, namely, the fact that a speaker has to specify a(ny) perspective on an event's result when processing causative events for verbalization.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Similarly, their event memory was boosted after verbalization of the scenes, independent of the specific forms uttered. This is a novel finding in the “thinking for speaking” literature: Whereas there is ample evidence for online attention biases induced by selection and retrieval of specific linguistic forms and structures (e.g., Bunger et al., ; Flecken, Carroll, Weimar, & van Stutterheim, ; Hendriks, Hickmann, & Demagny, ; Papafragou & Selimis, ; Papafragou et al., ; Slobin, ; Soroli & Hickmann, ), the present data suggest that these effects are not limited to such contexts. Here, a language‐specific effect surfaces regardless of the specific form in the linguistic output; it is driven by general requirements of Estonian grammar, namely, the fact that a speaker has to specify a(ny) perspective on an event's result when processing causative events for verbalization.…”
Section: Discussionsupporting
confidence: 51%
“…For example, speakers of satellite-framed languages typically mention the manner of motion, and they also allocate more visual attention to manner when watching and describing event videos, compared to speakers of verb-framed languages (e.g., Papafragou et al, 2008;Soroli & Hickmann, 2010). There is, however, not much evidence that such effects go beyond "thinking for speaking," that is, beyond the cognitive processes we engage in when preparing for verbalization (e.g., Bunger et al, 2016;Finkbeiner, Nicol, Greth, & Nakamura, 2002;Gennari et al, 2002;Montero-Melis et al, 2017;Papafragou et al, 2002Papafragou et al, , 2008Trueswell & Papafragou, 2010). Montero-Melis et al (2017) plausibly suggest that this may be caused by the large variability in motion event description, both within speakers of the same typological cluster, as well as across clusters.…”
Section: Event Cognition Cross-linguisticallymentioning
confidence: 99%
See 1 more Smart Citation
“…First, our aim was to test children's inferences about events on the basis of a single snapshot of the event. Second, prior developmental work has revealed that static depictions of events can elicit rich interpretations about events both in language production tasks and non-linguistic tasks from children of similar ages (Bunger et al, 2016;Göksun et al, 2011;Nappa, Wessell, McEldoon, Gleitman, & Trueswell, 2009;Ünal et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…How children identify events from visual experience is the topic of a small but growing literature on event perception (Baillargeon, Li, Gertner & Wu, 2011;Baldwin, Baird, Saylor, & Clark, 2001;Bunger, Skordos, Trueswell, & Papafragou, 2016;Göksun, Hirsh-Pasek & Golinkoff, 2010;Kominsky et al, 2017;Radvansky & Zacks, 2014;Spelke, Phillips & Woodward, 1995;Stahl, Romberg, Roseberry, Golinkoff, & Hirsh-Pasek, 2014;Tatone, Geraci, & Csibra, 2015;Ünal, Trueswell, & Papafragou, 2017) and a larger but separate literature on the acquisition of verbs labeling events of different types (Bowerman & Choi, 2001;Gleitman, 1990;Pinker, 1989;Fisher, Gleitman & Gleitman, 1991;Tomasello & Merriman, 2014, among many others). However, in this work events are typically visually available in their entirety.…”
Section: Introductionmentioning
confidence: 99%